Added mass evaluation with a finite-volume solver for applications in fluid–structure interaction problems solved with co-simulation. (August 2018) - Yvin, C.; Leroyer, A.; Visonneau, M.; Queutey, P.
Abstract: This work is devoted to the implementation and analysis of an efficient fluid–structure interaction coupling algorithm used in a cooperative simulation context for rigid bodies. This framework makes possible the study of complex fluid–structure configurations, through the coupling between CFD and dedicated multibody dynamics solvers. A specific focus is here laid on the characterisation of the numerical properties of the proposed coupling algorithm in terms of convergence speed and stability. In order to stabilise the segregated algorithm while keeping non-intrusive in the structure solver, a relaxation operator based on an artificial added mass technique is used. To compute an efficient relaxation operator, an original resolution of the added mass effect is implemented into the fluid finite-volume solver. Good convergence properties are observed for rigid bodies with six degrees of freedom even in case of strong destabilising added mass effects.